The quality of mental health literacy measurement tools evaluating the stigma of mental illness: a systematic review - Wei, Y. (Epidemiol Psychiatr Sci, 2017)
AIMS. Stigma of mental illness is a significant barrier to receiving mental health care. However, measurement tools evaluating stigma of mental illness have not been systematically assessed for their quality. We conducted a systematic review to critically appraise the methodological quality of studies assessing psychometrics of stigma measurement tools and determined the level of evidence of overall quality of psychometric properties of included tools. METHODS. We searched PubMed, PsycINFO, EMBASE, CINAHL, the Cochrane Library and ERIC databases for eligible studies. We conducted risk-of-bias analysis with the Consensus-based Standards for the Selection of Health Measurement Instruments checklist, rating studies as excellent, good, fair or poor. We further rated the level of evidence of the overall quality of psychometric properties, combining the study quality and quality of each psychometric property, as: strong, moderate, limited, conflicting or unknown. RESULTS. We identified 117 studies evaluating psychometric properties of 101 tools. The quality of specific studies varied, with ratings of: excellent (n = 5); good (mostly on internal consistency (n = 67)); fair (mostly on structural validity, n = 89 and construct validity, n = 85); and poor (mostly on internal consistency, n = 36). The overall quality of psychometric properties also varied from: strong (mostly content validity, n = 3), moderate (mostly internal consistency, n = 55), limited (mostly structural validity, n = 55 and construct validity, n = 46), conflicting (mostly test–retest reliability, n = 9) and unknown (mostly internal consistency, n = 36). CONCLUSIONS. We identified 12 tools demonstrating limited evidence or above for (+, ++, +++) all their properties, 69 tools reaching these levels of evidence for some of their properties, and 20 tools that did not meet the minimum level of evidence for all of their properties. We note that further research on stigma tool development is needed to ensure appropriate application.